At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To find the equation of a line that is parallel to the given line [tex]\(4x - y = -6\)[/tex] and passes through the point [tex]\((3, 9)\)[/tex], we can follow these steps:
### Step 1: Determine the slope of the given line
First, we will rewrite the equation of the given line [tex]\(4x - y = -6\)[/tex] in slope-intercept form [tex]\(y = mx + b\)[/tex]. This form makes it easier to identify the slope [tex]\(m\)[/tex].
Starting with the equation:
[tex]\[ 4x - y = -6 \][/tex]
Rearrange it to solve for [tex]\(y\)[/tex]:
[tex]\[ -y = -4x - 6 \][/tex]
[tex]\[ y = 4x + 6 \][/tex]
In the slope-intercept form [tex]\(y = mx + b\)[/tex], the coefficient of [tex]\(x\)[/tex] is the slope [tex]\(m\)[/tex]. Here, the slope [tex]\(m\)[/tex] is 4.
### Step 2: Use point-slope form to find the equation of the new line
We know that parallel lines have the same slope. Therefore, the line we are looking for has a slope of 4 and must pass through the point [tex]\((3, 9)\)[/tex].
We use the point-slope form of the equation of a line, which is:
[tex]\[ y - y_1 = m(x - x1) \][/tex]
Here, [tex]\((x_1, y_1)\)[/tex] is the point the line passes through and [tex]\(m\)[/tex] is the slope. Plugging in the known values:
[tex]\[ y - 9 = 4(x - 3) \][/tex]
### Step 3: Simplify to obtain the slope-intercept form of the equation
Now, we simplify the equation to get it into the slope-intercept form [tex]\(y = mx + b\)[/tex]:
[tex]\[ y - 9 = 4(x - 3) \][/tex]
[tex]\[ y - 9 = 4x - 12 \][/tex]
[tex]\[ y = 4x - 12 + 9 \][/tex]
[tex]\[ y = 4x - 3 \][/tex]
### Final Equation
The equation of the line that is parallel to [tex]\(4x - y = -6\)[/tex] and passes through the point [tex]\((3, 9)\)[/tex] is:
[tex]\[ y = 4x - 3 \][/tex]
### Step 1: Determine the slope of the given line
First, we will rewrite the equation of the given line [tex]\(4x - y = -6\)[/tex] in slope-intercept form [tex]\(y = mx + b\)[/tex]. This form makes it easier to identify the slope [tex]\(m\)[/tex].
Starting with the equation:
[tex]\[ 4x - y = -6 \][/tex]
Rearrange it to solve for [tex]\(y\)[/tex]:
[tex]\[ -y = -4x - 6 \][/tex]
[tex]\[ y = 4x + 6 \][/tex]
In the slope-intercept form [tex]\(y = mx + b\)[/tex], the coefficient of [tex]\(x\)[/tex] is the slope [tex]\(m\)[/tex]. Here, the slope [tex]\(m\)[/tex] is 4.
### Step 2: Use point-slope form to find the equation of the new line
We know that parallel lines have the same slope. Therefore, the line we are looking for has a slope of 4 and must pass through the point [tex]\((3, 9)\)[/tex].
We use the point-slope form of the equation of a line, which is:
[tex]\[ y - y_1 = m(x - x1) \][/tex]
Here, [tex]\((x_1, y_1)\)[/tex] is the point the line passes through and [tex]\(m\)[/tex] is the slope. Plugging in the known values:
[tex]\[ y - 9 = 4(x - 3) \][/tex]
### Step 3: Simplify to obtain the slope-intercept form of the equation
Now, we simplify the equation to get it into the slope-intercept form [tex]\(y = mx + b\)[/tex]:
[tex]\[ y - 9 = 4(x - 3) \][/tex]
[tex]\[ y - 9 = 4x - 12 \][/tex]
[tex]\[ y = 4x - 12 + 9 \][/tex]
[tex]\[ y = 4x - 3 \][/tex]
### Final Equation
The equation of the line that is parallel to [tex]\(4x - y = -6\)[/tex] and passes through the point [tex]\((3, 9)\)[/tex] is:
[tex]\[ y = 4x - 3 \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.